Pengaruh Pemasaran Digital dan Citra Destinasi Terhadap Keputusan Berkunjung Pada Wisata Bahari di Kepulauan Seribu - Ayu, Jati Paras (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
The purpose of this study was to examine the effect of digital marketing and destination image on the decision to visit the Thousand Islands. This study uses a type of quantitative qualitative research. The analytical method of this research is multiple regression analysis. The population in this study were domestic and foreign tourists who visited the Thousand Islands, amounting to 800,390 people. While the sample in this study amounted to 205 people. The sampling technique used is simple random sampling because the sampling is done randomly without regard to the existing strata in the population. The results of a partial study of digital marketing and destination image have a significant effect on visiting decisions. Promotional media with digital marketing are useful for tourists in getting easy information about tourist destinations to be visited, anytime and anywhere. To build the image of a destination in the minds of consumers, it certainly doesn't just disappear, but there needs to be consistency, uniqueness and vigorous promotion. The implementation of the promotion of marine tourism in the Thousand Islands must be promoted on Instagram, Facebook, Twitter and YuoTube because almost all internet users are users of these social media. Keywords: The Influence, Digital Marketing, Destination Image, Visit Decision